Formation of H2O2/temperature dual-responsive supramolecular micelles for drug delivery and kinetics. Issue 12 (13th August 2021) - Ma, Songmei; Li, Guiying; Tao, Qian; Guo, Lei; Zhou, Zaishuai; Yu, Jiahui
Abstract: H2 O2 and temperature dual-responsive supramolecular micelles were prepared from β-cyclodextrin-poly( N -isopropylacrylamide) (β-CD-PNIPAM) star polymer and ferrocene-modified polyethylene glycol (Fc-mPEG) due to the host–guest recognitions between cyclodextrin and ferrocene. The micelles with the size of about 100 nm were comprised of hydrophobic PNIPAM as the core and hydrophilic mPEG as the shell at the temperature above LCST. The supramolecular micelles exhibited reversible temperature and redox on–off switch feature. The hydrophobic micelles core and cavity of β-CD can effectively encapsulate doxorubicin (DOX) with the drug-loading content of 37.23% and entrapment efficiency of 74.45%. The drug-loaded micelles exhibited higher anti-cancer activity than free drugs. The ferrocene group was oxidized into ferrocene ions when H2 O2 was added, resulting in the dissociation of supramolecular micelles and acceleration of drug release. Release kinetics of DOX conforms to oxidation controlled mechanism with H2 O2 and Fickian diffusion-controlled mechanism with temperature. Graphical Abstract: UF0001